(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Perineal wound pain is discomfort that occurs in postpartum mothers. Based on clinical practice experience in PMB Dince Safrina, 70% of postpartum mothers complained of pain and feeling uncomfortable. One of the alternatives to reduce perineal wound pain is sitz bath therapy. This study was to determine the effect of sitz bath therapy on perineal wound pain in postpartum mothers. This quasy experimental study used one group pre-test and posttest design. This research was conducted at PMB Dince Safrina in March-June 2019. The population was all 6-hour postpartum mothers who had perineal wound at PMB Dince Safrina with a sample size of 17 taken by purposive sampling technique. The method of data collection was observation with an observation sheet that contained a scale of pain intensity measurement using the Numeric Rating Scale (NRS). The results showed that the average intensity of perineal wound pain before and after sitz bath therapy was 5.59 (SD 0.939) and 2.47 (SD 0.943). The results of statistical tests using Wilcoxon on the 95% confidence level found that there was an effect of sitz bath therapy on the intensity of perineal wound pain in postpartum mothers (p value = 0.000). It is recommended for midwives to consider sitz bath therapy as an alternative in the provision of nonpharmacological care to reduce the intensity of perineal wound pain in postpartum mothers.